Xiao Lu: asserting her voice through artistic practice - Moner, Laia Manonelles (Revista Brasileira de Estudos da Presença, 2023)
At the opening of the iconic exhibition China/Avant-Garde (1989, Beijing), the artist Xiao Lu fired two shots at her installation Dialogue and handed the gun to the artist Tang Song, who would later become her boyfriend. From that moment on, the artworld attributed the piece to Tang Song and Xiao Lu. Two decades after the event, Xiao Lu disputed the unique authorship of the artwork in a fictional memoir, Dialogue (2010). In this text, she presented a historiography of her art, reflecting on the performance and challenging Tang Song’s appropriation of the work. This article explores Xiao Lu’s re-writing of the official history of art and its patriarchal foundations through a feminist lens. It engages with complementary, contradictory, and contrasting readings of Xiao Lu's art and offers a new approach that addresses both the therapeutic and political dimensions of the artist's autobiographical account.